PERAN GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DALAM PEMBENTUKAN KARAKTER PROYEK PENGUATAN PROFIL PELAJAR PANCASILA SEKOLAH MENENGAH ATAS DI KABUPATEN PURWOREJO - Arfi Nabela, Yana; Qoriah, Anirotul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to understand the role of Physical Education, Sports, and Health (PJOK) teachers in the Project for Strengthening the Pancasila Student Profile (P5) within the Merdeka Curriculum in fostering character education among public senior high school students in Purworejo Regency. This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The results of the study indicate that the role of Physical Education, Sports, and Health teachers has not yet fully supported the development of students’ character through the Project for Strengthening the Pancasila Student Profile (P5). This is reflected in the limited number of implemented dimensions that have not been carried out optimally, as well as the fact that only three schools in Purworejo Regency have been able to convey and implement the program effectively. The implication of this study highlights the need for greater socialization and training regarding the P5 program for school principals and teachers, as well as the provision of adequate resources to support the implementation of the P5 project.